Analysis of a Bidirectional DC-DC Converter with High Voltage Gain - Behrouz Razzaghzadeh; Mahdi Salimi (Institute of Advanced Engineering and Science, 2015)
A novel bidirectional DC-DC converter with high conversion ratio is proposed in this paper. The proposed converter uses the three windings coupled-inductor to achieved high voltage conversion ratio. The primary side consist of a winding and secondary side consist of two windings, which these two windings are series to achieved high voltage gain.In the boost mode, a capacitor is parallel charged and series discharged by the coupled inductor. Thus, high step-up voltage gain can be achieved with an appropriate duty ratio. In the buck mode, a capacitor is series charged and parallel discharged by the coupled inductor. The bidirectional converter can have high step-down voltage gain.The stress voltage of main switches can be reduced, and efficiency can be improved. The operating principle and the steady-state analyses of the voltage gain are discussed. Finally, in 24V for low voltage, and 400V for high voltage, and 200W for output power, this converter is simulated in MATLAB.